Influence of the metal phase of novel Al₂O₃/TiO₂/TiAl₂O₅ composites obtained via the slip casting method - Wachowski, Marcin; Zygmuntowicz, Justyna; Kosturek, Robert; Śnieżek, L.; Piotrkiewicz, P.; Żurowski, Radosław; Korycka, Karolina (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
This study aims to analyze the ceramic-metal composite Al2O3/TiO2/TiAl2O5 obtained using the slip-casting method. Samples containing 50% of the solid phase and 2% and 4% fractions of the metallic phase were examined. Rheological investigations were performed. Measurements of shrinkage and density of the composites produced were determined. The phase composition of the obtained composite was investigated using SEM/EDS and XRD techniques. Stereological analysis was performed as well. The slip-casting method enables the production of the proposed composite, reinforced by the presence of TiO2 and TiAl2O5. With the increase in the content of the metallic phase in the composite, the thialite phase content increases, but relative density and volumetric shrinkage of the obtained composites both decrease. Thialite grains are characterized by a size in the range of 4 µm to 15 µm, which leads to a low density of the samples. The results revealed that no significant effect of changing the metal phase content of the slurries used for the composites being fabricated was observed on the limiting grain growth of alumina during the sintering process of slip-casting composites. This finding is important as it suggests that the increase in metallic phase content does not lead to undesirable grain coarsening, which could degrade mechanical properties.